COMPARATIVE EVALUATION OF HEMODYNAMIC CHARACTERISTICS IN PATIENTS WITH RHEUMATOID ARTHRITIS AND ARTERIAL HYPERTENSION - Y. E. Teregulov; D. K. Husainova; D. I. Abdulganeeva; S. D. Mayanskaya (Столичная издательская компания, 2015)
Aim. To study the peculiarities of hemodynamic disorders in patients with rheumatoid arthritis (RA) and arterial hypertension (HT), and in patients with hypertension but without RA using the integral indicators of arterial stiffness.Material and methods. The study included 106 RA patients (group 1), among them 83 (78%) women and 23 (22%) men, mean age 45.3±10.3 years. The group of comparison (group 2) included 63 patients (22 (35%) women and 41 (65%) men, mean age 47.9±12.8 years) with HT stages 1-3. The control group (group 3) consisted of 32 healthy volunteers: 19 women and 13 men, mean age 24.7±5.34 years. All patients underwent ECG and echocardiography. The model of cardiovascular system was used to calculate the modulus of volume elasticity (MVE), mean arterial blood pressure (BP) and total peripheral vascular resistance (TPR); stroke volume and cardiac output were measured using echocardiography.Results. Significant differences in the parameters of BP, arterial stiffness and TPR were identified in patients with RA and HT as compared with the patients of the control group. Arterial stiffness in RA patients with HT, as well as without it, was significantly higher and TPR was lower than in hypertensive patients. RA patients with HT were older and had significantly higher values of cardiac output than those without HT. In RA patients hyperkinetic type of hemodynamics was observed in 53.8% of the cases, eukinetic - in 34.9%, hypokinetic - in 11.3%. Hypertensive patients had same types of hemodynamics in 3.2%, 61.9%, and 34.9%, respectively. In healthy people hyperkinetic type was observed in 22.9% of the cases, eukinetic - in 65.6%, hypokinetic - in 12.5%.Conclusions. RA patients as compared with healthy people had significantly higher arterial stiffness indices regardless of BP. At that, hyperkinetic type of hemodynamics prevailed in RA patients, while in hypertensive patients and healthy people - the eukinetic one. Increased stroke volume and cardiac output at high arterial stiffness can be one of the causes of HT in RA patients.